A Service Perspective on Work with Vulnerable Children: Frontline Staff’s Perceptions of how Management Affects Value Creation - Westrup, Ulrika; Danielsson, Pernilla (Scandinavian Journal of Public Administration, 2019)
This article investigates frontline staff’s perceptions of how management affects theirview of value creation during day-to-day work with vulnerable children. The empirical data is based on dialogues during 15 meetings with 8 welfare professionals fromeducation, social services, and children’s and adolescent psychiatry. The analyticalapproach used in this article makes use of the service dominant logic (SDL) as a conceptual framework for studying frontline staff’s perceptions. The findings indicate that perceptions of management affect the staff’s view of value creation in orientationssuch as: (1) the delivery of ready-made expert solutions, (2) the simplification of value- creation processes, and (3) disconnected service systems. Overall, one conclusion drawn is that the SDL can be used as an analytical approach to understanding and exploring value creation in welfare services, thus contributing towards developing managerial applications for supporting frontline staff to a greater extent from a service perspective; however, there are some definite limitations.